Patterns and Treatment Modalities of Maxillofacial Fractures due to Motorcycle Accidents - Tariq Sardar, Umer Ullah, Ajmal Khan, Zainab Shah, Anjum Iqbal, Hina Afsar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Maxillofacial fractures due to motorbike accidents are common in Pakistan. The aim of current study was to evaluate the pattern of fractures in motorbike accidents and the common treatment modalities used to deal these fractures. Methodology: In this cross-sectional study 274 patients with facial fractures were recruited consecutively from Maxillofacial surgery unit of Khyber College of Dentistry, from April 2021 to December 2021. Patterns were classified broadly into midface, mandible and combined fractures while treatment modalities included close reduction and ORIF at 1, 2, 3 and 4 or more points. Simple descriptive statistics were used with SPSS version 20.0. Chi-Square and Fisher’s Exact tests were applied where required, with p>0.05 kept as significant. Results: Out of 274 patients, 260 were male and 110 belonged to age group 21 to 30years. Mandible fracture (n=108) was the most common pattern followed by combined fractures (n=88). Symphysis/parasymphysis was the most common site of single mandibular fractures while most common single midfacial bone to fracture was ZMC (n=56). Overall 2 points fixation (n=88) was the most common treatment modality used followed by 1 point fixation (n=72). Mandibular fractures were treated mostly by single point fixation and combined fractures by ORIF at 3 or more points (p=0.000). Conclusion: Maxillofacial fractures due to motorbike accident are common in men of 21 to 30 years age. Mandibular fractures are the most common followed by combined fractures. Mandibular fractures require 1 point, midface fractures 2 points and combined fractures 3 or more points fixation for their optimal management.